1994
DOI: 10.1109/23.340597
|View full text |Cite
|
Sign up to set email alerts
|

Total dose effects on negative voltage regulator

Abstract: Functional failure at low dose level (4 Krad(Si)) on voltage regulators (LM137) from different manufacturers are analysed. Dose rate effects on parts hardness are evaluated, showing that lowering the dose rate degrade more the ICs in the range 55 rad(Si)/s-0,s rad(Si)/s A failure mechanism is proposed, mainly based on circuit analysis, voltage contrast measurements, local irradiation and local electrical measurements with probe station. A spice simulation was performed, providing quantitative informations on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(13 citation statements)
references
References 3 publications
0
11
0
2
Order By: Relevance
“…В литературе этот эффект часто обозначают в сокращенном виде ELDRS. Впервые этот эффект наблюдали еще в на-чале 1990−х годов [44][45][46][47], но до сих актуальность данной тематики не снизилась. Эффект ELDRS имеет большое значение для разработки космических си-стем.…”
Section: эффекты длительного низкоинтенсивного облученияunclassified
“…В литературе этот эффект часто обозначают в сокращенном виде ELDRS. Впервые этот эффект наблюдали еще в на-чале 1990−х годов [44][45][46][47], но до сих актуальность данной тематики не снизилась. Эффект ELDRS имеет большое значение для разработки космических си-стем.…”
Section: эффекты длительного низкоинтенсивного облученияunclassified
“…The results obtained from this test can be used to discriminate the influence of the TID on the evolution of the amplifiers although the application of these results is not immediate since the dose rate is increased as well. In fact, there is a lot of works that demonstrate that the damage caused by TID in typical op amp parameters may be 10-20 times larger in low dose rate tests than in accelerated ones [19], [20]. However, another paper reports that the slew rate of a typical op amp, the LM124, is not very sensitive to the enhanced low dose rate ef-fect [21]; e.g., at a TID value of 1 kGy(Si), V OS , I B & I OS showed an enhanced damage factor on the order of 10-20 from high to ultra-low dose rate whereas in the case of slew rate the enhanced damage factor was only 2-3.…”
Section: E Tid Testsmentioning
confidence: 99%
“…One of them is the radiation behavior of linear circuits depending upon the type of input stage, i.e., bipolar, FET or MOS-based. Linear bipolar devices, particularly those with pnp stages show a significant degradation at dose rates lower than 10 mrad(Si)/s [2]- [4]. It has been shown that pnp and substrate-pnp (spnp) input structures have been observed to deteriorate more than those with npn super-structures and are much less damaged for the same radiation levels [5].…”
Section: Literature Reviewmentioning
confidence: 99%